Personality disorders, but not cancer severity or treatment type, are risk factors for later generalised anxiety disorder and major depressive disorder in non metastatic breast cancer patients. (28th February 2016) - Champagne, Anne-Laure; Brunault, Paul; Huguet, Grégoire; Suzanne, Isabelle; Senon, Jean-Louis; Body, Gilles; Rusch, Emmanuel; Magnin, Guillaume; Voyer, Mélanie; Réveillère, Christian; Camus, Vincent
Abstract: This study aimed to determine whether personality disorders were associated with later Major Depressive Disorder (MDD) or Generalised Anxiety Disorder (GAD) in breast cancer patients. This longitudinal and multicentric study included 120 French non-metastatic breast cancer patients. After cancer diagnosis (T1) and 7 months after diagnosis (T3), we assessed MDD and GAD (Mini International Neuropsychiatric Interview 5.0). We assessed personality disorders 3 months after diagnosis (VKP). We used multiple logistic regression analysis to determine what were the factors associated with GAD and MDD at T3. At T3, prevalence rate was 10.8% for MDD and 19.2% for GAD. GAD at T3 was significantly and independently associated with GAD at T1 and with existence of a personality disorder, no matter the cluster type. MDD at T3 was significantly and independently associated with MDD at T1 and with the existence of a cluster C personality disorder. Initial cancer severity and the type of treatment used were not associated with GAD or MDD at T3. Breast cancer patients with personality disorders are at higher risk for GAD and MDD at the end of treatment. Patients with GAD should be screened for personality disorders. Specific interventions for patients with personality disorders could prevent psychiatric disorders. Highlights: Anxiety (GAD) and depressive disorders (MDD) are frequent in breast cancer patients. Patients with GAD (or MDD) at diagnosis are at higher risk for later GAD (or MDD). Breast cancer patients with any personality disorder are at higher risk for GAD. Patients with cluster C personality disorders are at higher risk for later MDD. Cancer severity and type of treatment used were not associated with later GAD or MDD.